Impact of “The Blob” and “El Niño” in the SW Baja California Peninsula: Plankton and Environmental Variability of Bahia Magdalena - Jiménez-Quiroz, María del Carmen; Cervantes-Duarte, Rafael; Funes-Rodríguez, René; Barón-Campis, Sofía A.; García-Romero, Felipe de Jesús; Hernández-Trujillo, Sergio; Hernández-Becerril, David U.; González-Armas, Rogelio; Martell-Dubois, Raúl; Cerdeira-Estrada, Sergio; Fernández-Méndez, José I.; González-Ania, Luis V.; et al. (Frontiers in Marine Science, 2019)
Bahia Magdalena is a coastal lagoon located in the Pacific coast of Baja California, a transitional zone between tropical and temperate regions. Its biological and fishing richness is enormous. The objective of this work was to determine the impact of the unusual and consecutive warming events knows as The Blob (TB2013-2015) and 2015-2016 El Niño on the hydrological characteristics and plankton communities, the lower levels of the trophic web. The changes we observed strongly suggested that the warming caused by those phenomena did affect the hydrology and phyto and zooplankton communities. This study included analyses of environmental and biological variables measured in situ and with MODIS-Aqua satellite images, from January 2015 to December 2017. In 2015, the air temperature was very high, upwelling strength decreased and temperature, salinity and water density showed the tropical influence. Additionally, the percentage of oxygen saturation and the nutrients and chlorophyll-a (Chl-a) concentrations were low and showed intra-annual variations different to usual. By April 2015, the chain-forming diatom Eucampia zodiacus bloomed, and we did not record an autumn bloom, but Chl-a fluorescence suggested that smaller phytoplankton fractions were predominant in that season. Zooplankton biomass (ZB) was lower since the second semester of 2015 and showed a negative trend until 2017. Relatively low percentages of dead zooplankton (%ZD) were also recorded. In 2016, when El Niño declined, and the ENSO cold phase (La Niña) started, there were an enhancing of upwellings, nutrients, and Chl-a concentrations. Blooms of diatoms occurred in spring and autumn (Guinardia/Rhizosolenia), whereas the ZB remained low, but %ZD was very high. La Niña finished in 2017, and in contrast to previous years, the upwelling's phenology was close to 1967-2010 average, and upwelling strength increased. Therefore, its rich-nutrients waters input caused several diatoms blooms, whereas ZB remained scarce.